Prostate adenocarcinoma with unilateral testicular metastasis: Two cases with different presentations - Musliu Adetola Tolani; Muhammed Ahmed; Ahmad Bello; Balarabe Kabir; Lovely Fidelis; Hussaini Yusuf Maitama (Nigerian Journal of Medicine, 2020)
Background: Most patients with prostate cancer present with advanced disease in sub-Saharan Africa. However, metastasis to the testis is rare. Findings: This report details the incidental detection of isolated unilateral metastasis to the testis and epididymis from the prostate on histopathologic analysis of the orchidectomy specimen in a 77-year-old man (case 1) and the finding of palpable unilateral testicular secondary from aggressive metastatic prostate cancer in a relatively younger man (47 years old) during clinical evaluation (case 2). Conclusion: The presentation of testicular metastasis from prostate cancer varies with the patient. A high index of suspicion in the phases of evaluation of these patients is required in order to prevent missed diagnosis.